Vigilância à saúde da criança na perspectiva dos enfermeiros da estratégia saúde da família - Yakuwa, Marina Sayuri [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This qualitative study aimed at apprehending conceptualizations and at describing experiences of nurses working in the Family Health Strategy in a medium-sized city in São Paulo state in relation to Children’s Health Surveillance, with a special focus on nursing consultation. Data were collected from 12 nurses by means of recorded semi-structured interviews that were analyzed according to the Thematic Content Analysis Method. Results were systematized into four themes: Conceptualizations about Children’s Health Surveillance; Children’s Health Surveillance in the practice of the Family Health Strategy; Nursing consultation and Children’s Health Surveillance; Proposals to qualify Children’s Health Surveillance in the realm of the Family Health Strategy. It was possible to apprehend amplified and actual conceptualizations of Children’s Health Surveillance as well as to describe experiences surrounded by difficulties to incorporate the premises of this form of Children’s Health Care in the Family Health Strategy. Nursing consultation was noteworthy as a privileged moment, but not unique, to develop such practice. Finally, based on nurses’ proposals, the importance of triggering permanent education processes targeted at these themes in family-health services was considered

Este estudo de abordagem qualitativa objetivou apreender concepções e descrever experiências de enfermeiros da Estratégia Saúde da Família de um município de médio porte do interior paulista sobre Vigilância à Saúde Infantil, com especial enfoque na consulta de enfermagem. Os dados foram coletados junto a 12 enfermeiros, por meio de entrevistas semi-estruturadas gravadas, sendo analisados segundo o Método de Análise de Conteúdo, vertente Temática. Os resultados foram sistematizados em quatro temas: Concepções sobre Vigilância à Saúde Infantil; Vigilância à Saúde Infantil na prática da Estratégia Saúde da Família; Consulta de enfermagem e a Vigilância à Saúde Infantil; Propostas para qualificar a Vigilância à Saúde Infantil no âmbito da Estratégia Saúde da Família. Foi possível apreender concepções ampliadas e atuais sobre Vigilância à Saúde Infantil, bem como descrever experiências permeadas por dificuldades para incorporar as premissas dessa forma de Atenção à Saúde da Criança na Estratégia Saúde da Família. A consulta de enfermagem se destacou como um momento privilegiado, mas não único, para se desenvolver essa prática. Com base nas propostas dos enfermeiros, por fim, considera-se a importância de se desencadear processos de educação permanente, nas unidades de saúde da família, voltados a essa temática
Keywords: Enfermeiros; Criança – Cuidado e higiene; Vigilância sanitária